Novel Ligand and Device Designs for Stable Light-Emitting Electrochemical Cells Based on Heteroleptic Copper(I) Complexes - Fresta, Elisa; Volpi, Giorgio; Milanesio, Marco; Garino, Claudio; Barolo, Claudia; Costa, Rubén D (Inorganic chemistry, 2018)
This work reports on the positive impact of (i) attaching methoxy groups at the ortho position of the bipyridine ligand (6,6'-dimethoxy-2,2'-bipyridine) in heteroleptic copper(I) complexes belonging to the [Cu(bpy)(POP)] family, and (ii) a new device design comprising a multilayered architecture to decouple hole/electron injection and transport processes on the performance of light-emitting electrochemical cells (LECs). In short, the substituted complex showed enhanced thermal- and photostability, photoluminescence, and ionic conductivity features in thin films compared to those of the archetypal complex without substitution. These beneficial features led to LECs outperforming reference devices in terms of luminance, stability, and efficacy. Furthermore, a new device design resulted in a 10-fold enhancement of the stability without negatively affecting the other figures of merit. Here, hole/electron injection and transport processes are performed at two different layers, while electron injection and electron-hole recombination occur at the copper(I) complex layer. As such, this work provides further insights into a smart design of N^N ligands for copper(I) complexes, opening the path to a simple device architecture toward an enhanced electroluminescence response.